Superconductive supercooling and superheating of small cadmium spheres: Size effects. - Francisco De la Cruz, M.; Maloney, D.; Cardona, M. (American Chemical Society's, 1971)
Fil: Francisco De la Cruz, M. Comisión Nacional de Energía Atómica; Argentina